Pengaruh Jenis Media Tanam Terhadap Pertumbuhan Dan Hasil Tanaman Sawi Pagoda (Brassica narinosa L) Varietas Ta Ke Cai F1 Pada Hidroponik Sistem Wick - Adhiprawira, Devantara; Sugiono, Darso; Laksono, Rommy Andika (Jurnal Ilmiah Wahana Pendidikan, 2026)
Pagoda mustard (Brassica narinosa L.) variety Ta Ke Cai F1 is a nutritious leafy vegetable with great potential for hydroponic cultivation. The wick hydroponic system offers an efficient and simple alternative, especially for communities with limited land. One of the key factors in hydroponic cultivation is the choice of growing media, as it influences nutrient absorption, aeration, and root development. Therefore, this study aims to evaluate the effects of various types of growing media on the growth and yield of pagoda mustard in a wick hydroponic system.. The study was conducted at the Taiwan Technical Mission Greenhouse, Karawang, using a Completely Randomized Design (CRD) with one factor, consisting of 10 types of growing media and 3 replications: M0 (Rockwool), M1 (Coconut Husk), M2 (Fern Roots), M3 (Peat Moss), M4 (Banana Stem), M5 (Coconut Husk + Fern Roots), M6 (Coconut Husk + Peat Moss), M7 (Coconut Husk + Banana Stem), M8 (Fern Roots + Peat Moss), and M9 (Fern Roots + Banana Stem). The observed parameters included plant height, number of leaves, root length, leaf area, fresh weight with roots, and fresh weight without roots. The results showed that Peat Moss (M3) and the combination of Fern Roots + Peat Moss (M8) had the most significant positive effects on all observed growth and yield parameters. Peat moss was found to be superior due to its high water-holding capacity, good aeration, and nutrient availability that supports plant development. In contrast, banana stem-based media (M4, M7, M9) resulted in the lowest performance, which was presumably caused by the compact structure of the media and the presence of undecomposed toxic compounds such as tannins and lignin. It can be concluded that peat moss and its combination with fern roots are effective growing media for wick hydroponic systems in Pagoda Mustard cultivation, as they significantly enhance vegetative growth and yield.